Punching behaviour of foam filled modular sandwich panels with high-density polyethylene skins. (January 2021) - Tahmoorian, F.; Nemati, S.; Sharafi, P.; Samali, B.; Khakpour, S.
Abstract: Modular composite panels are being widely used for floors and roofs in prefabricated construction. Scissors shear and punching shear strength are two critical parameters for designing the sandwich panels under concentrated out of plane load. However, there are relatively few studies on scissors shear and punching shear strength of sandwich panels in literature in comparison with tensile strength and normal shear strength. In this paper, the scissor shear and punching behaviour of an innovative structural sandwich panel is investigated. The introduced system consists of a high-density polyurethane (PUR) foam core as well as two continuous layers of high-density polyethylene (HDPE) facings. Scissors shear strength and punching strength of these panels are studied through a creative experimental procedure. The scissors shear test is also simulated using non-linear finite element models and finally, the results are compared with each other. The results show that the first yield point of composite happens due to shear stress in foam. On the other hand, due to scissors shear, the foam is ruptured on two surfaces at about 45°. The scissors shear strength for the proposed panel, is determined to be 3.1 MPa, which is in good agreement with numerical results. In addition, the results revealed that using studliner skins can improve the scissors shear strength and punching shear strength of panels by about 34% and 22%, respectively. Highlights: Scissor shear (punching) behaviour of a foam filled panel is investigated. Tests for material characterization and punching behaviour were conducted on both foam and sandwich sections. Finite element analysis was performed for the design of section and results were checked against tests results. The results can be used for the design of floors and roofs under point loads.